Rounding the answer is 100.
Answer:
4
Step-by-step explanation:
-6 + x = -2
add 6 to each side
-6 +6 +x = -2 +6
x = 4
Factors are (y - 7)(5y - 43)
Step-by-step explanation:
- Step 1: Given, 5x² + 12x + 4 = (x + 2)(5x + 2)
Now, to factor 5(y - 9)² + 12(y - 9) + 4. Here, y - 9 can be equated to x if both equations are compared.
- Step 2: To factorize, substitute y - 9 for x in the factors (x + 2)(5x + 2)
⇒ Factors = (y - 9 + 2)[5(y - 9) + 2]
= (y - 7)(5y - 45 + 2)
= (y - 7)(5y - 43)
Well you can see it would be mixed number and it is not a number less than 1